2015
DOI: 10.1007/s41105-015-0037-3
|View full text |Cite
|
Sign up to set email alerts
|

Self-help therapy for sleep problems in hospital nurses in Japan: a controlled pilot study

Abstract: The present pilot study examined the effectiveness of self-help therapy (SHT) in hospital nurses in Japan. Twenty-five hospital nurses (22 female, mean age 39.7 ± 14.6 years) participated in a 90-min workshop covering sleep hygiene education and brief stress management. After the workshop, participants in the SHT group (n = 10) were asked to practice good sleep habits, relaxation techniques, and keep a sleep diary, whereas participants in the control group (n = 15) were not. Pre- and post-test questionnaires, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 15 publications
1
17
2
Order By: Relevance
“…The mean score of sleep of the nurses was 7.29 ± 3.66 which was consistent with the study by Akbari et al (4). Many studies reported the mean score of sleep quality of nurses as greater than 5 (2, 15, 26) which was higher than the quality of sleep score of ordinary individuals (4,26). Through the comparison of the results of these studies it can be concluded that the quality of sleep of nurses is poor.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The mean score of sleep of the nurses was 7.29 ± 3.66 which was consistent with the study by Akbari et al (4). Many studies reported the mean score of sleep quality of nurses as greater than 5 (2, 15, 26) which was higher than the quality of sleep score of ordinary individuals (4,26). Through the comparison of the results of these studies it can be concluded that the quality of sleep of nurses is poor.…”
Section: Discussionsupporting
confidence: 87%
“…There was a higher rate of sleep disorders in the elderly. In other studies, older people were less able to adapt to night shifts (26,33,34). Therefore, early retirement is recommended for nurses, so that younger people who have more ability to adapt to circadian rhythm disorders can be employed.…”
Section: Discussionmentioning
confidence: 98%
“…For instance, a survey of 636 nurses from seven hospitals of different levels in Spain showed 6.80 ± 3.39 29) . A study in Japan found that 109 nurses in general hospitals had a sleep score of 6.0 ± 2.1 30) . This Insert Table 3 Insert Table 4 may be associated with a strong hidden risk of mental diseases.…”
Section: Current Situation Of Sleep Quality Among Psychiatric Nursesmentioning
confidence: 99%
“…Neglect of sleep quality due to work or maladaptive sleep hygiene practice may predispose HCW to various adverse health outcomes (Peach et al, 2016;Nakada, Sugimoto, Kadotani & Yamada, 2018). While the use of medications may be helpful as a short term measure, the nonpharmacological methods would be ideal for a long term solution to promote better sleep quality Kaku et al, 2012;Morimoto et al, 2016).…”
Section: Introductionmentioning
confidence: 99%